Isolation of multiantennary N-glycans from glycoproteins for hepatocyte specific targeting via the asialoglycoprotein receptor. Issue 100 (12th October 2016) - Witzigmann, Dominik; Detampel, Pascal; Porta, Fabiola; Huwyler, Jörg
Abstract : The asialoglycoprotein receptor (ASGPR) expressed on parenchymal liver cells specifically binds multivalent carbohydrates from desialylated glycoproteins. Abstract : The asialoglycoprotein receptor (ASGPR) expressed on parenchymal liver cells specifically binds multivalent carbohydrates from desialylated glycoproteins. This feature offers a huge potential for hepatocyte specific drug targeting. In this study, multiantennary N -glycans from asialofetuin have been isolated to actively target the asialoglycoprotein receptor on human hepatocellular carcinoma cells in vitro .